(3TQM GdbUjOI GddGejIs - (3CHh HcQ Hf eMeO Hf CMeO GdHSJis; (3Ydj GdSYjOj GdTgjOj GdGhSjs ((3fYeI Hf eYde jhbOjf eMehO TeWQGHi s)
(3ChdgG (B:s
(3QCjJ gPg GdbUjOI GdGejI Ydi bhGYO Cgd GdSfI hGdLeGYI ef EfTGA Ydi GdSYjOi GdTgjOi GdChSi abO TQYJ ai JCdjag hTQMg s
(3BNQgG (B:s
(3hef fSH Gddg JYGdi Zdi Gddhe hGdXe , abO Vd VdGdkG HYjOkG Je GdbUjOI s
(3HgG fXGe GdJYbjHIs
(3Ydi bhGYO Cgd GdSfI hGdLeGYIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdJhMjO hGdedd hGdfMds